A Juridical Analysis of the Title Revocation of Senegal's 2025 AFCON: A Review of Walk-out Sanctions under CAF Regulations - Marselius Nataniel Situmeang; Vincentius Hansel Darmawan; Ahmad Dyfan Nadhif Islamy (Faculty of Law Universitas Negeri Surabaya, 2025)
This study analyzes the juridical conflict surrounding the revocation of the Senegal National Team’s 2025 Africa Cup of Nations (AFCON) championship title by the Confédération Africaine de Football (CAF). The research focuses on the